Truncated ARQ Based Cooperative Transmission Initialization - Khan, Faisal Raisham; Shahid, Dr. Muhammad Khalil (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A communication is energy efficient when the communicating peers are near to each other or where the separating distances are short and the LOS component is a dominant one. The channel conditions in wireless communication vary with respect to time and distance. Let us consider a scenario where a terminal X is communicating to another terminal Y in a shadowed fading environment through an access point (AP) or a base station (BS). Supposing that the terminal X is at the border of the transmission range of BS, any slight movement of the terminal X may result in either degradation of the wireless channel between terminal X and BS or totally getting out of transmission radius of BS. The MAC layer of BS fails to receive the error-free packet as a result. The BS does not send back the ACK packet to the source terminal X. After waiting for a time specified, the source starts retransmitting the packet. If the source terminal does not receive the ACK packet even after a threshold number of retransmissions (RetryLimit), the source discards the packet. An efficient and reliable scheme of retransmission is proposed in this paper by using STBC based relay transmission system. MATLAB is used for simulation purpose and the results generated for direct and cooperative transmissions are compared in terms of the link layer parameter PER.